REDUCING THE NUMBER OF PACKAGING IN THE CODING PROCESS AT PACKAGING UNIT USING THE SIX SIGMA METHOD - Nurcahyanie, Yunia Dwie; Rusdiyantoro (Tibuana, 2019)
Non-dairy creamer is a product made at PT. NDC as a substitute for milk or cream, which is a fat emulsion product. Krimer is packed with a 25kg small bag with an updated coding according to the lot, production time, production date, product name, and packaging date expiration date. Often there is an error in the packaging unit, especially at the coding stage with the wrong non-dairy creamer packaging code that causes packaging defects. The defects in packaging focused on the coding stage, have to be minimized. The research uses the Six Sigma method as a useful tool to increase productivity and product quality. With DMAIC Discussion (Define, Measure, Analyze, Improve, and Control). Through data processing and analysis using the DMAIC cycle obtained three types of packaging defects, namely cryptic code, double code and wrong code from the three defects obtained percentage value of cryptic code 63%, double code 44% and wrong code 42% and obtained an average value sigma 3.71 with a DPMO value of 13,553